Mariana Pineda: uma revolucionária na recriação de Frederico García Lorca - Santos, Alexandre Nunes dos (2014)
MARIANA PINEDA: A REVOLUTIONARY IN RECREATION OF FEDERICO GARCÍA LORCA García Lorca analyzes the dramatic transposition of the political process of the eponymous heroine grenadine. Celebrated in popular songs who sing their fight, Mariana edge a liberal flag during the government of Don Fernando VII to please the man she loved, and ends up being convicted and executed. Lorca composes a dramatic play based on elements of the character that make telluric discussion intrinsically human affairs from his heroine, with her embroidery, stands for love and freedom. Mariana Pineda who inspires Lorcas s artistic production lived in the early nineteenth century, and served in the fight against a dictatorship, conducting partisan political actions, which committed her to the despotic government of her time. The heroine defends her values of honor and freedom, common feature of other female characters in the traditional Spanish theater, especially the dramaturgist of the Golden Age. Lope de Vega is focused due to telluric features, appreciation of the female and elements of folk tales that gets close to the lorquiano drama. Therefore, a comparative study of the project of the two Spanish authors built on the drama under study Mariana Pineda by Lorca and tragicomedy Fuenteovejuna by Lope de Vega will be held.